TELAAH PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA PENGANIAYAAN BERAT DALAM PUTUSAN NOMOR 209/PID.B/2023/PN.SKT - Bahapasca, Danam Isyafara; Rustamaji, Muhammad (Verstek, 2025)
This study analyzes to determine the role and power of experts in the evidentiary examination process in the fraud case of decision Number 717/Pid.B/2023/PN.Bdg and to find out the judge's legal considerations in decision Number 717/Pid.B/2023/PN.Bdg. in accordance with the provisions of Article 183 of the Criminal Procedure Code. This study analyzes is normative legal research that is prescriptive and applied. This research uses a case study approach and a legislative approach. The sources of legal materials used are primary legal materials and secondary legal materials. The technique for collecting legal materials uses library study techniques. Legal material analysis techniques are processed using the deductive syllogism method. Based on the research results, it was found that the evidentiary strength value of expert testimony in Decision Number 717/Pid.B/2023/PN.Bdg is the same as the evidentiary strength value attached to the witness statement evidence. The evidentiary strength value attached to expert testimony evidence has the independent evidentiary strength value. And the judge's considerations were in accordance with the provisions of Article 183 of the Criminal Procedure Code